Gathering of information in Internet environment: balancing the right to discovery and right to protect the privacy under the laws - Mohamed, Duryana (International Association of Computer Science and Information Technology Press (IACSIT), 2013)
Gathering of information in the internet environment is very challenging since the information may be available at different places. There are many methods to gather information and one of it is by way of discovery of document. This discovery process is adopted when preparing one's case for a full trial. It is used to gather information which is not adequate and the party needs to get relevant documents from the opposite party as to complete his case. The opposite party in the suits may be an individual, company, government agency or its servant. When the court order for discovery the opposite party is expected to comply with it but in some cases, the opposite party refuses to do so citing privacy issue as his or their reason for refusal. The issues are how to effectively implement discovery against them and how to balance between the right to discovery and right to protect the privacy of their clients. What is actually their liability towards the plaintiff and what are the consequences of failure to comply with discovery order. This paper will discuss and analyse the above issues by presenting laws and court decisions pertaining to discovery of documents as practiced in Malaysia and several other countries.